2018
DOI: 10.1063/1.5018351
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic reconnection in the low solar chromosphere with a more realistic radiative cooling model

Abstract: Magnetic reconnection is the most likely mechanism responsible for the high temperature events that are observed in strongly magnetized locations around the temperature minimum in the low solar chromosphere. This work improves upon our previous work ["Magnetic Reconnection in Strongly Magnetized Regions of the Low Solar Chromosphere", The Astrophysical Journal 852, 95 (2018) ] by using a more realistic radiative cooling model computed from the OPACITY project and the CHI-ANTI database. We find that the rate of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…Judge [2015] performed an independent analysis and suggested that these events were formed in the low to middle chromosphere or above. While Ellerman bombs are phenomena that are well known to be signatures of magnetic reconnections in the photosphere [Ellerman, 1917;Vissers et al, 2015;Reid et al, 2016;Fang et al, 2006;Hong et al, 2014;Nelson et al, 2013Nelson et al, , 2015Nelson et al, , 2016Fang et al, 2017;Ni et al, 2016Ni et al, , 2018a, have crosschecked IRIS observations and Hα images of 10 TR UV burst events from the Chinese New Vacuum Solar Telescope [Xu et al, 2014;Liu et al, 2014] and have found that 6 of the 10 events are associated with Ellerman bombs in the photosphere and the rest 4 are not. This indicates that some UV bursts in the TR are signatures of magnetic reconnections in the photosphere that heat plasma up to at least the TR temperature [Kim et al, 2015;.…”
Section: Uv Bursts In the Trmentioning
confidence: 99%
“…Judge [2015] performed an independent analysis and suggested that these events were formed in the low to middle chromosphere or above. While Ellerman bombs are phenomena that are well known to be signatures of magnetic reconnections in the photosphere [Ellerman, 1917;Vissers et al, 2015;Reid et al, 2016;Fang et al, 2006;Hong et al, 2014;Nelson et al, 2013Nelson et al, , 2015Nelson et al, , 2016Fang et al, 2017;Ni et al, 2016Ni et al, , 2018a, have crosschecked IRIS observations and Hα images of 10 TR UV burst events from the Chinese New Vacuum Solar Telescope [Xu et al, 2014;Liu et al, 2014] and have found that 6 of the 10 events are associated with Ellerman bombs in the photosphere and the rest 4 are not. This indicates that some UV bursts in the TR are signatures of magnetic reconnections in the photosphere that heat plasma up to at least the TR temperature [Kim et al, 2015;.…”
Section: Uv Bursts In the Trmentioning
confidence: 99%
“…For example, the solar chromosphere is relatively cool, dense, and weakly ionized, but contains many classes of dynamical events thought to be driven by reconnection, such as UV bursts [2,3], jets [4,5], spicules [6,7], or transition region explosive events [8]. The importance of partially ionized reconnection to chromospheric physics has motivated several studies of partially ionized reconnection [9][10][11][12][13][14][15][16][17][18][19][20]. However, a major open question is under what conditions fast (i.e., Alfvénic and resistivity independent) reconnection can occur.…”
mentioning
confidence: 99%
“…This indicates that some UV bursts in the TR are signatures of magnetic reconnections in the photosphere that heat plasma up to at least the TR temperature [Kim et al, 2015;. Such a conclusion has also been confirmed by [Nelson et al, 2017], who established that some Ellerman bombs in the quiet Sun also have responses in the IRIS Si IV lines. It is worth mentioning that the blends of the chromospheric absorption lines in the TR emission lines might also be the results of cold plasma (such as filaments, mini-filaments) at the foreground [Vissers et al, 2015;Huang et al, 2017], and thus it is not complete criteria for this species of UV bursts.…”
Section: Uv Bursts In the Trmentioning
confidence: 54%
“…Judge [2015] performed an independent analysis and suggested that these events were formed in the low to middle chromosphere or above. While Ellerman bombs are phenomena that are well known to be signatures of magnetic reconnections in the photosphere [Ellerman, 1917;Vissers et al, 2015;Reid et al, 2016;Fang et al, 2006;Hong et al, 2014;Nelson et al, 2013Nelson et al, , 2015Nelson et al, , 2016Fang et al, 2017;Ni et al, 2016Ni et al, , 2018a, have crosschecked IRIS observations and Hα images of 10 TR UV burst events from the Chinese New Vacuum Solar Telescope [Xu et al, 2014;Liu et al, 2014] and have found that 6 of the 10 events are associated with Ellerman bombs in the photosphere and the rest 4 are not. This indicates that some UV bursts in the TR are signatures of magnetic reconnections in the photosphere that heat plasma up to at least the TR temperature [Kim et al, 2015;.…”
Section: Uv Bursts In the Trmentioning
confidence: 99%
See 1 more Smart Citation